2022
DOI: 10.1021/acs.est.2c03695
|View full text |Cite
|
Sign up to set email alerts
|

Method Development for Separation and Analysis of Tire and Road Wear Particles from Roadside Soil Samples

Abstract: A comprehensive understanding of tire and road wear particles (TRWPs) and their detection and quantification in soils is still challenged by the lack of well-set standardized methods, inherent technological inconsistencies, and generalized protocols. Our protocol includes soil sampling, size separation, and organic matter removal by using hydrogen peroxide followed by density separation and analysis. In this context, roadside soil samples from different sites in Kansas and Ohio, USA, were collected and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…Although TRWPs, as one of the largest sources of microplastics, are the main contributors to terrestrial microplastics (45%), 45 there has been insufficient research on the presence of 6PPDQ in soil. In a study investigating the occurrence of rubber-derived quinones in air, water, and soil in Hong Kong, China, 6PPDQ was detected in roadside soil samples.…”
Section: Occurrence In Other Mediamentioning
confidence: 99%
“…Although TRWPs, as one of the largest sources of microplastics, are the main contributors to terrestrial microplastics (45%), 45 there has been insufficient research on the presence of 6PPDQ in soil. In a study investigating the occurrence of rubber-derived quinones in air, water, and soil in Hong Kong, China, 6PPDQ was detected in roadside soil samples.…”
Section: Occurrence In Other Mediamentioning
confidence: 99%
“…Vegetable oils are indispensable in polymeric coatings in terms of alkyds, polyester aides, polyether amides, polyurethanes, epoxies, and polyols majorly used in the coatings industry. Further, vegetable oils such as castor, tung, corn, soybean, and linseed have widely been reported as comonomers in various reported research works and for varied applications like coatings, plasticizers, and elastomers. , However, the focus of this review is to explore the challenges, progress, and opportunities with vegetable oil epoxide applications exclusively. That is, the regular use of vegetable oil as such, or with other functionalization, to be used in polymer products are not part of the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the automobile industry’s share of 40% global pollution, tire contributes to a hefty 20–30%. , Tire manufacturing also contributes to carbon dioxide emissions and the depletion of petrochemical resources . Several studies also show an ubiquitous presence of the much-discussed tire and road wear particles (TRWP) in the air, water, and soil. TRWP quantification studies show that 1 000 000 ton/yr of TRWP has been reported in the U.S. alone. , Further, several degradation studies of tire particles show that tire leachate from the additives can be present in the environment after prolonged exposure. Moreover, TRWP is shown to have environmental implications like human health risk on the liver and kidneys and respiratory irritation, and acute toxicity on aquatic life such as the coho-salmon species. Thus, there is a primal need for sustainable formulation by incorporating more environmentally friendly materials. Any material that meets the general product requirements without compromising the future generation’s ability to meet their needs is referred to as a sustainable material .…”
Section: Introductionmentioning
confidence: 99%